Curcumin Alleviates Epidermal Psoriasis-Like Dermatitis and IL-6/STAT3 Pathway of Mice - Cai Z; Zeng Y; Liu Z; Zhu R; Wang W (Dove Medical Press, 2023)
Zhenguo Cai,1,2,* Yibin Zeng,3,* Zhuohang Liu,3 Ruizheng Zhu,3 Wuqing Wang1,3 1Department of Dermatology, Shuguang Hospital, Shanghai University of Traditional Chinese Medicine, Shanghai, 201203, People's Republic of China; 2Department of Dermatology, Changhai Hospital, Naval Medical University, Shanghai, 200433, People's Republic of China; 3Department of Dermatology, Minhang Hospital, Fudan University/Central Hospital of Minhang District, Shanghai, 201199, People's Republic of China*These authors contributed equally to this workCorrespondence: Wuqing Wang; Ruizheng Zhu, Email wangwuqing121@sina.com; bigbigworld_emilia@163.comBackground: To further investigate why curcumin (CUR) can attenuate psoriasis-like dermatitis of mice.Methods and Results: Sixteen mice were randomized into four groups. The control group used carrier cream, and the model and the CUR group were applied with topical 5% imiquimod in the naked mice skin once a day for 6 days (62.5 mg/day/mice). Meanwhile, the control and model mice were given the same dose of saline by oral means, while mice in the CUR groups received oral drug doses of 50 and 100 mg/kg once a day for 6 days, respectively. CUR could largely improve imiquimod-induced lesions of mice. By using the ELISA and qPCR, we found that the protein and mRNA levels of epidermal TNF-α and IL-6 were inhibited by CUR. The phosphorylation levels of STAT3 and its downstream associated protein levels (eg, Cyclin D1, Bcl-2 and Pim1) in skin tissues of different groups were also inhibited by CUR. Furthermore, the results of immunohistochemistry also showed the repressed effect of CUR for the expression of TNF-α, IL-6 and p-STAT3 in psoriasis-like lesions of mice.Conclusion: CUR can effectively ameliorate the featured lesions of psoriasis mice, which may be closely associated with the involvement of IL-6/STAT3 signaling.Keywords: curcumin, psoriasis, IL-6/STAT3, inflammation